2010
DOI: 10.21649/akemu.v15i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pattern of Urinary Stone Disease in Our Setting

Abstract: Objectives:To study the basic clinical pattern of urinary stone disease in our setting.Study design: Descriptive study. Subjects: A total of 257 urolith patients with different stone burden enrolled in the study.Methodology: Structured and standardized history and clinical investigations collected in all of urolith patients. The diagnosis of stone disease was based on history, physical examination followed by KUB x-ray, ultrasonography and IVU .All patients subjected to open stone surgery. The data were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…et al(20) observed the mean age at onset of urinary stone as 25.8 years which is not consistent with the observation made in the present study. In Iran, the mean age at presentation was 41.5±16.3 years and the peak incidence was between 55 and 65 years (21).Memon et al reported that the male to female ratio in urinary stone disease was 230:100(20).…”
contrasting
confidence: 96%
See 1 more Smart Citation
“…et al(20) observed the mean age at onset of urinary stone as 25.8 years which is not consistent with the observation made in the present study. In Iran, the mean age at presentation was 41.5±16.3 years and the peak incidence was between 55 and 65 years (21).Memon et al reported that the male to female ratio in urinary stone disease was 230:100(20).…”
contrasting
confidence: 96%
“…In Iran, the mean age at presentation was 41.5±16.3 years and the peak incidence was between 55 and 65 years (21).Memon et al reported that the male to female ratio in urinary stone disease was 230:100(20). Basiri et al who investigated the demographic profile of urolithiasis across Iran observed that male-to-female ratio was 138:100 (21).…”
mentioning
confidence: 99%
“…22 Authors reported flank pain, hematuria and dysuria as the main presenting symptoms of urolithiasis, which is also the case in our study. [2][3][4]12,14,25,30 Apart from this, a study conducted by Odzebe et al and Rimtebaye et al found a high rate of acute urinary retention in their review (26.5% and 28.7%). 3,21 This variation can be explained by the high incidence of lower tract stone and obstructive conditions in their patients.…”
Section: Discussionmentioning
confidence: 90%
“…7 Comparable with this, our study and others also confirmed urolithiasis as a male predominant disease. 2,4,5,9,10,12,13,15,25,26,[28][29][30] Males are assumed to be susceptible to stone formation for reasons such as lithogenic effect of testosterone, uro-genital anatomy which is prone to stasis and engagement in strenuous work which results in dehydration unless adequately replaced. 14,19,24,31 The limited opportunity of women to go to a health facility in our setup was also mentioned as a factor for the male predominance in urolithiasis.…”
Section: Discussionmentioning
confidence: 99%
“…However in the study of Jan Muhammad Memon was reported that Out of 257 patients 181 (70.42%) were male and 76 (29.56%) female with male to female ratio of 2.3:1. 18 In our study there was wide variation of age ranging from a minimum of 15 year to 45 years in both group. The mean age was 32+ 2.1years.…”
Section: Resultsmentioning
confidence: 49%